Postoperative Delirium in Older Inpatients: A survey of Nursing Staff Knowledge - Verma, Anant Kumar (Asian Journal of Medical Research, 2019)
Background: Postoperative delirium is common in the elderly and is associated with poor outcome. However, its diagnosis is often missed or delayed. Nursing staff is at the frontline and plays a crucial role in the early detection and management of delirium. This study was designed to explore the knowledge and attitudes of nursing staff about delirium in the scope of an educational program implementation. Subjects and Methods: Qualitative and quantitative analyses conducted in four surgical wards and one intensive care unit in an Academic Hospital in India. A questionnaire was administered to 121 nurses and nursing assistants and semi structured interviews were conducted. Results: A total of 89 questionnaires were completed (response rate of 73.55%). Regarding symptoms, most of the nursing staff knew about disorientation and incoherent speech. However, few knew about acute onset and fluctuation, and the hypoactive form of delirium was virtually unknown. Regarding risk factors, while many knew about dehydration, drug use and the use of physical restraints, few knew about sensory impairment and infection. The staff globally knew about the main prevention measures, but knowledge on patient management was especially poor. Finally, no respondent knew about or used the Confusion Assessment Method. The qualitative analysis revealed a trivialization of delirium onset among older inpatients and the continuity of preconceived ideas on delirium, its diagnosis and its risk factors. Conclusion: This study provides a clearer understanding of staff learning needs and identifies potential issues to be addressed in order to increase future intervention efficacy.